OE CAI: COMPUTER-ASSISTED INSTRUCTION OF OLD ENGLISH - Alcaraz Sintes, Alejandro (International Journal of English Studies, 2002)
This article offer a general but thorougli survey of Computer Assisted lnstruction as applied to the Old English language íkoni the work of the late 80's pioneers to December 2001. It enibraces all the different facets of the question: stand-alone and web-based applications, Internet sites. CD-ROMs, grammars, dictioriaries, general courses, reading software, extralinguistic material, exercises, handouts, audio files ... Each instruction itee whether it be a website, a java exercise, an online course or an electronic book- is reviewed and URLs are provided in Sootiiotes. These reviews are accompanied all throughout by the pertinent theoretical background and practical advice.